Characterizing the Electronic Structure of Chemical Elements through Atomic Graph Representations - Ousmane Barry; Mamadou Yaya Balde; Souleymane Balde; Aboubacar Safie Sylla; Mamadou Saliou Diallo; Ousmane Wora Diallo (Scientific Research, New Technologies and Applications Vol. 5, 2024)
Teaching and mastering atomistic concepts has long been a major preoccupation for teachers and learners at the secondary and undergraduate levels. The abstract nature of atomistic concepts is, in fact, the crux of the problem. In an effort to address this concern, a characteristic graph of the atom has been designed to lift the veil and simplify the learning of these concepts. This graph provides a general explanation of the different concepts of atomics. Each concept is interpreted by specific graphics derived from the first. To revolutionize, in a simpler way, the establishment of the electronic structure, special graphs are also designed. This concept, which illustrates order and period, is based on stability and has led to the classification of chemical elements into stacks. The electron distribution of the heaviest atom “118e” led to new methods of illustrating classification, known as “condensed tables”, with or without period and sub-layer order. A new criterion for classifying chemical elements is the distribution of electrons according to the order of the energy level of the sublayers, noted as “OE”. This leads to the so-called “condensed order table”. This condensed table summarizes all types of ordered classification. This distribution of electrons along the x-axis “n” leads analogously to a condensed period table, which also summarizes all periodic classifications. These two very similar but different condensed tables are a new and innovative way of illustrating the classification of chemical elements. In addition, the “Condensed Order Table”, built around a new classification criterion, OE, leads to a new classification, called the “Order Table”. Beyond this result, the present work highlights the existence of a numerical series whose enlightened reading helps explain the concepts of atomistics. These value series make it easier to establish the electronic structure, even by mental calculation, of the 118 elements in a single line. These different value series with periods: 2, 8, 8, 18, 18, 32, 32, and with order: 2, 2, 8, 8, 18, 18, 32, 30 have made it possible to achieve this objective.